Characterization of an allotriploid strawberry Fragaria × bifera Duchesne (Rosaceae) from Europe - Houshang Nosrati; Adam H. Price; Pedro Gerstberger; Chris C. Wilcock (Natura Sloveniae)
Allopolyploidy has played an important role in the plant evolution. To assess its role in speciation, it is necessary to examine fertility and crossability of hybrids. A hybrid clone of the genus Fragaria with different and complex morphology compared to F. vesca, F. viridis and F. moschata, was detected in Germany (in Bayreuth, Bavaria). The genome size of these plants was measured using flow cytometry and their fertility was tested in experimental crossing. The parental origin of the hybrid was revealed using RAPD approach. From the mean intensity of fluorescence emitted by PI-stained nuclei for F. moschata, F. vesca, F. viridis and the hybrid, triploidy of the hybrid could be indicated. The hybrid shared an 1800bp and 880bp long species-specific RAPDs bands with F. viridis and F. vesca, respectively, indicating them as the parental species of the hybrid. The hybrid did not produce any fruit in selfing, open pollination and when crossed by pollen of F. vesca and F. viridis, all showing female sterility of the hybrid. The hybrid had 78% pollen sterility, however, pollinating F. vesca by pollen of the hybrid produced viable seed and F1 plants, indicating its male fertility. This work shows allopolyploidy role in the evolution and speciation of Fragaria, and may suggest the study site as potential new centre of Fragaria speciation.